Alinhamento das estratégias do planejamento e controle da manutenção (PCM) com as finalidades e funções do planejamento e controle da produção (PCP): uma abordagem analítica - Souza, José Barrozo de (2008)
The Maintenance and Operation as the most relevant administrative and operational functions of production, besides having the responsibility of making it right (quality advantage), making it fast (speed advantage), making it on time (reliability advantage), changing what is being done (flexibility advantage) and making it cheap (cost advantage), have gain impulse lately and are now at the center of several important activities because of their vital role, for example, in the areas of security, preservation of the environment, productivity, marketing, quality, reliability and accounting systems. With this new vision, great changes and opportunities are being presented for those sectors of the Operation and Maintenance. In the new paradigm, the Maintenance and Operation teams are motivated to strategically preserve the full operation of the productive and organizational system, not just preserving the equipment for the equipment. Actually, it develops an effective strategy to increase the offering assets of the company, thus achieving the goals of the Production Planning and Control within the company. The main purpose of this thesis is to examine the alignment of the strategies of the Maintenance Planning and Control with the purposes and functions of the Production Planning and Control. For this reason, a bibliographic study was done, according to the technique of the Content Analysis. Finally, the analysis of the research directs to some contributions of significant character, for example, to the areas of strategy and logistics of organizations that work, especially, within high levels of competitiveness environments. Basically, the analysis points to the positive impact of alignment on parameters such as: support of competitive strategy, productivity, cost, reliability and availability of physical assets and flexibility of the productive organizational system. And it emphasizes that the alignment is possible in medium and large companies.